Exploring Learners’ Needs and Expectations: Translating EU Texts in an English Bachelor’s Programme at a Hungarian College - Károly, Adrienn (Working Papers in Language Pedagogy, 2011)
This paper reports on a needs analysis study involving a group of Hungarian undergraduate students of English before taking an EU specialized translation course. The purpose of the study was to explore the students’ needs regarding course content and methodology, to capture their perceptions about the translation process and translation competence, and to compare these with the teachers’ expectations and assumptions as well as with the current course syllabus. The results of the study are hoped to be of assistance to the teacher of the course in selecting and adapting the course content, material and teaching approaches to the immediate needs of the students. Data was collected through questionnaires with the students and a semi-structured oral interview with their teacher. Document analysis was also used to compare the students’ expressed goals, needs, and perceptions with the aims and contents of the course as stated in the course syllabus. The results show that undergraduate students’ needs and perceptions – regarding translation in general and one particular course – are different from the teachers’ assumptions and the aims of the course as expressed in the syllabus. Therefore, exploring undergraduate students’ actual needs and tailoring the course to these needs is a crucial step in syllabus design.